Tools for assessing lung fluid in neonates with respiratory distress - So Jin Yoon; Jung Ho Han; Kee Hyun Cho; Joonsik Park; Soon Min Lee; Min Soo Park (BMC, 2022)
Abstract Background Transient tachypnea of the newborn (TTN), as a common cause of neonatal respiratory distress, needs to be distinguished from respiratory distress syndrome (RDS). Various modalities such as lung ultrasonography, cytokine analysis, and electrical cardiometry for the evaluation of lung fluid can be helpful for the exact diagnosis, however, clinical diagnosis has been applied mainly. This study aimed to evaluate the usefulness of the various tools for the diagnosis of TTN and RDS in neonates. Methods This study evaluated 22 late-preterm and term infants admitted to the neonatal intensive care unit of Gangnam Severance Hospital because of respiratory distress. Total 9 neonates were diagnosed with TTN and 13 had RDS. In addition to chest radiography, the LUS score was calculated by a neonatologist using the portable ultrasound device. Cytokines in the bronchoalveolar lavage fluid supernatant were measured. Thoracic fluid content was measured using an electrical cardiometry device. Results We enrolled 22 patients with median gestational age, 37.1 weeks, and birth weight 3100 g. There is no difference in patient characteristics between RDS and TTN group. Lung ultrasound score was significantly higher in RDS than TTN (11 vs 6, p = 0.001). Score 0 is shown in all infants with TTN. Score 1 is shown as significantly more in RDS than TTN. Between the TTN and RDS groups, there were significant differences in the changes of thoracic fluid content (2 vs − 1.5, p < 0.001), IL-1β levels (2.5 vs 11.3, p = 0.02), and TNF-α levels (20.1 vs 11.2, p = 0.04). Conclusion We found lung ultrasound and electrical cardiometry to be reliable diagnostic tools for assessing infants with respiratory distress among late-preterm and term infants. Further studies with a large number of patients are needed to confirm their clinical usefulness.